Isolated biliary tract injury: necessity to heighten vigilance following blunt abdominal trauma in children (Journal of Ideas in Health, 2025)
Background: Bile duct injury after blunt abdominal trauma is a rare entity in the pediatric population. Its occurrence has been highly linked to the primary injuries of the liver or duodenum as explained by their anatomical affiliation. Case presentation: Here we present a case of a 4-year-old female brought in with a history of generalized abdominal pain that was associated with distension and absolute constipation. This was preceded by a blunt abdominal traumatic incident four days prior. On examination, she was ill-looking, tachypneic, and had a grossly distended abdomen with a positive Blumberg's sign. After the baseline laboratory and radiographic investigations, she was taken for exploration where Bile peritonitis was found secondarily to a perforated common bile duct (CBD). All other visceral structures and organs were fine; a meticulous primary closure of the 2 by 1 cm defect was done as superimposed by an omental patch. She fared well post-operatively and was discharged on the seventh day.Conclusion: Though rare, biliary tract injury should always be considered among the differential diagnoses in blunt abdominal trauma, as its early diagnosis precipitates early intervention which will in turn positively affect the patient's outcome.
Keywords: Biliary Tract, Abdominal Trauma, Children, Biliary Leak, Bile Peritonitis, Blumberg’s Sign, Tanzania